Cultivation of CNPA G3 sesame irrigated with saline water and fertilized with nitrate-N and ammonium-N - Geovani S. de Lima; Adaan S. Dias; Lauriane A. dos A. Soares; Hans R. Gheyi; José P. Camara Neto; Luan D. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The study aimed to evaluate the effects of irrigation with saline water and fertilization with nitrate (NO3--N) and ammonium (NH4+-N) ratios on growth, flowering, water consumption and water use efficiency of the sesame cv. CNPA G3. The treatments were distributed in randomized blocks in a 5 x 5 factorial with three replicates, referring to five levels of electrical conductivity of the irrigation water - ECw (0.6, 1.2, 1.8, 2.4 and 3.0 dS m-1) and nitrate (NO3--N) and ammonium (NH4+-N) (200/0, 150/50, 100/100, 50/150, 0/200 mg kg-1) ratios. Irrigation with saline water above 0.6 dS m-1 inhibited the growth, delayed flowering and promoted early maturation of capsules of sesame, cv. CNPA G3. The proportion of 0/200 mg kg-1 of NO3--N/NH4+-N promoted the greatest increase relative to stem diameter and height of sesame plants. Water consumption decreases with increasing ECw and was significantly lower in plants fertilized with the proportion of 0/200 of NO3--N/NH4+-N. The interaction between ECw levels and ammonium/nitrate proportions significantly affect water use efficiency, and the highest value was obtained with ECw of 0.6 dS m-1 and fertilization with 150:50 mg kg-1 of NO3--N and NH4+-N.